New Discovery of Myeloid-Derived Suppressor Cell’s Tale on Viral Infection and COVID-19 - Park, Soo-Jeung; Nam, Da-eun; Seong, Hae Chang; Hahn, Young S. (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are generated under biological stress such as cancer, inflammatory tissue damage, and viral infection. In recent years, with occurrence of global infectious diseases, new discovery on MDSCs functions has been significantly expanded during viral infection and COVID-19. For a successful viral infection, pathogens viruses develop immune evasion strategies to avoid immune recognition. Numerous viruses induce the differentiation and expansion of MDSCs in order to suppress host immune responses including natural killer cells, antigen presenting cells, and T-cells. Moreover, MDSCs play an important role in regulation of immunopathogenesis by balancing viral infection and tissue damage. In this review article, we describe the overview of immunomodulation and genetic regulation of MDSCs during viral infection in the animal model and human studies. In addition, we include up-to-date review of role of MDSCs in SARS-CoV-2 infection and COVID-19. Finally, we discuss potential therapeutics targeting MDSCs.